ANALYSIS OF RISK FACTORS FOR DELAYED DIAGNOSIS IN PULMONARY TUBERCULOSIS CASES IN BENGKULU CITY - Putri, Marissa Aurelya; Mirna; Sundari, Mulya; Nugraheni, Enny (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2024)
This study aims to analyse the factors associated with delayed diagnosis of Pulmonary Tuberculosis and the frequency distribution of TB patients. The research method was analytic-observational with cross sectional approach. The research sample was patients in Bengkulu City total of 64 respondents. The results of the analysis showed that the majority of TB patients were male, age group 16-25 years, people who had jobs, and secondary education, had initial symptoms of cough, lived in the central area of the city, the distance from home to the nearest health facility was 1 < 2 km, had a good level of knowledge, the majority had low stigma towards TB disease. There was no significant association between delay in diagnosis and gender, age, education, income, occupation, distance from home to health centre, location of residence, initial symptoms, first action of health centre, first health service visited. There was a significant association between the time between initial symptoms and seeking treatment and the incidence of delayed diagnosis. However, there was no significant association between delayed diagnosis, patient stigma about TB disease and knowledge.